Estudo teórico das propriedades estruturais e eletrônicas das monocamadas de nitreto de gálio decorada com H ou F adicionadas de defeitos - Gomes, Djardiel da Silva (2024)
Research on two-dimensional (2D) materials has gained momentum in recent years due to new physical properties with great technological applicability. In this thesis, we investiga- ted the structural stability and electronic properties of gallium nitride monolayers decorated with hydrogen or fluorine and compared the results obtained with the pure GaN monolayer, through the formalism of density functional theory (DFT). To expand the range of possible applications, we introduced vacancy and chemical substitution defects in the decorated struc- tures, since it is well known that the introduction of these defects induces the appearance of notable electronic behaviors. From our results, the adsorption of atoms to the gallium nitride monolayer increases the structural stability statically. Furthermore, it is possible to verify that insertion defects in the pure monolayer induce notable changes in the bandgap in these monolayers. Finally, we discovered that a useful property of the GaN monolayer is that after fluorine adsorption, this monolayer becomes more resistant to redox.